Intelligent Mushroom Monitoring System - Pravinth Raja, S; P.Roger Rozario, A; Nagarani, S; S.Kavitha, N (International Journal of Engineering and Technology, 2018)
Mushrooms are classified as vegetables in the food world, but they are actually fungi. Although they are not vegetables, mushrooms provide several important nutrients and they have a very important part in the food market. Mushrooms are enriched in nutrients and they possess medical benefits such as decrease the risk of obesity and overall mortality, diabetes, and heart disease. The main barriers for the high yield is the defects in primitive methods that is being used. The research applied the use of Internet of Things with sensors to measure and monitor the temperature, humidity, CO2 in the mushroom farm. The collected data is checked with the bound values and triggers the actuators accordingly. The intense monitoring eventually leads to increased yield.Â  The system utilizes sensor technology to optimize climate condition for optimum growth.Â Â
Keywords: mushroom; IoT smart farm; sensor technology